2014
DOI: 10.1515/jpm-2014-0134
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin utilization for labor induction in obese and lean women

Abstract: To determine if oxytocin dosage used for labor induction differed in obese and lean women, we analyzed records of patients who underwent term labor induction and delivered vaginally. Each of a cohort of 27 patients with a body mass index (BMI) >40 kg/m2 was matched with a patient with a BMI <28 kg/m2 for gestational age, for birth weight, and for cervical dilatation and fetal station at admission. The oxytocin dose administered during first stage labor was calculated for each patient. In addition to the matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…Oxytocin augmentation was not different in the present study. In contrast to this finding, previous investigations found higher doses of oxytocin necessary during induction of labor and labor in obese women …”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Oxytocin augmentation was not different in the present study. In contrast to this finding, previous investigations found higher doses of oxytocin necessary during induction of labor and labor in obese women …”
Section: Discussioncontrasting
confidence: 85%
“…Similar results were reported by Lassiter et al , but they did not stratify for parity . Further studies investigated the length of labor and did not find any difference . Multiple analysis demonstrated that BMI as well as parity, gestational age, and Bishop score were associated with induction‐to‐delivery interval.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This effect was seen in Hill M et al study as well. In a retrospective review, amongst a cohort of 54-term women undergoing induction of labor with subsequent vaginal deliveries, obese women (BMI > 40 kg/ m 2 ) required more oxytocin than lean women during the first stage of labor when matched for parity, diabetes, epidural use, birth weight, pre-induction dilatation, and station [9]. In attempts of explaining this phenomenon, HajagosToth et al reviewed the influences of increased body weight on multiple endocrine and paracrine systems.…”
Section: Resultsmentioning
confidence: 99%